Photochemically induced thrombosis combined with chronic restraint stress for modeling post-stroke depression in mice - Tuersunjiang, Tumarisi; Wang, Qingchen; Wang, Zhengzheng; Gao, Feng; Wang, Zhengchun (Frontiers in Neuroscience, 2025)
IntroductionPost-stroke depression (PSD) is a prevalent neuropsychiatric disorder associated with impaired recovery in stroke survivors, potentially linked to dysregulation of brain-derived neurotrophic factor (BDNF). This study aimed to establish a novel animal model of PSD by integrating ischemic brain injury with chronic psychological stress.MethodsMice were subjected to photochemically induced thrombosis (PIT) to generate focal ischemic lesions in the parietal lobe, followed by chronic restraint stress (CRS) to simulate post-stroke psychological stress. Behavioral assessments (sucrose preference test, forced swim test, tail suspension test) and molecular analyses (BDNF, synaptophysin [SYP], interleukin-1 [IL-1], tumor necrosis factor-α [TNF-α]) were conducted to evaluate depressive-like phenotypes and neuroinflammatory markers.ResultsThe PIT model produced consistent ischemic damage, with an average infarct area of 2.580 ± 0.426% in the parietal lobe. Mice exposed to PIT-CRS exhibited significant depressive-like behaviors, including reduced sucrose preference (p < 0.001), increased immobility time in the forced swim test (p = 0.056), and prolonged immobility in the tail suspension test (p = 0.168) compared to the Sham group. Molecular analyses revealed marked downregulation of BDNF (p = 0.004) and SYP (p = 0.074), alongside upregulated IL-1 (p = 0.024) and TNF-α (p = 0.368) levels in the PIT-CRS group.ConclusionThe PIT-CRS model provides a comprehensive and reproducible platform for studying PSD. By integrating both ischemic injury and chronic stress, this model captures the multifaceted nature of PSD and offers valuable insights into its pathophysiology. Future research using this model could pave the way for the development of targeted therapies for PSD.